2014
DOI: 10.1115/1.4027898
|View full text |Cite
|
Sign up to set email alerts
|

Combustion and Emission Characterization of n-Butanol Fueled HCCI Engine

Abstract: Com bustion and Em ission C haracterization of n-B utanol Fueled HCCI EngineBiofuels are attracting global attention as alternate transportation fuels due to advan tages of their being produced from locally available renewable resources, lower pollution potential, and biodegradable nature. Butanol is fast emerging as one of the competitive biofuels for use in transportation engines. Homogeneous charge compression ignition (HCCI) engines have shown great potential for higher engine efficiency and ultralow NOx a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…In Ref. [5,6], it is shown that butanol can be paired with homogeneous charge compression ignition combustion mode.…”
Section: Free-piston Linear Generator Systemmentioning
confidence: 99%
“…In Ref. [5,6], it is shown that butanol can be paired with homogeneous charge compression ignition combustion mode.…”
Section: Free-piston Linear Generator Systemmentioning
confidence: 99%